Efektifitas Pengadaan Bahan Makanan dalam Penentuan Harga Jual - I Gusti Ngurah Agung Wiryanata (JURNAL GASTRONOMI INDONESIA, 2022)
This research focuses on the effectiveness of food procurement in determining the selling price at FPBS Bali hotel. Food procurement that affects the variance between standard food costs and actual food costs will affect the profit of the food and beverage department. This research uses a qualitative descriptive method, namely research that in the process uses systematic techniques to understand, reduce, process, and draw conclusions from qualitative data collected based on interviews, and observations. The results showed that: the purchasing department purchases food ingredients not competitively but based on supplier loyalty. Receiving food ingredients lacks quality and quantity checks in accordance with the standard purchase specifications set by the hotel. Food storage activities have not fully run properly such as not paying attention to temperature and the use of the FIFO method. The recording of food expenditure from the store has not been maximum using the storeroom requisition (SR). Determination of the selling price of food mark-up pricing approach, namely setting the price of the product by taking into account all material costs and the expected profit level has not been used for the entire food menu.